From In Vivo Predictive Dissolution to Virtual Bioequivalence: A GastroPlus®-Driven Framework for Generic Candesartan Cilexetil Tablets - Hao Ruan; Xiaoting Geng; Zijing Situ; Qian Shen; Tianjian Ye; Xin Chen; Weike Su (Pharmaceuticals)
Background: Candesartan cilexetil, a Biopharmaceutics Classification System (BCS) II prodrug, demonstrates compromised bioavailability attributable to its limited aqueous solubility coupled with P-glycoprotein (P-gp)-mediated efflux and hepatic first-pass metabolism, thereby introducing complexities in generic drug bioequivalence assessments. With the rapid advancement of computational technologies, the integration of biorelevant dissolution methodologies with physiologically based pharmacokinetic (PBPK) modeling is emerging as a transformative paradigm in advancing bioequivalence evaluation strategies for generic drug products. This study presents a GastroPlus®-driven framework integrating in vivo predictive dissolution (IPD) and virtual bioequivalence (VBE) to evaluate the quality consistency of generic candesartan cilexetil tablets. Methods: By developing an oral PBPK model in GastroPlus®, we established an IPD method using a phosphate-buffer-based flow-through cell dissolution apparatus. In vitro dissolution profiles of generic tablets from four manufacturers were measured and incorporated into the model to perform VBE simulations. Results: The results demonstrated that only the product from Company A achieved virtual bioequivalence with the reference product, aligning with real-world quality consistency assessments. Conclusions: The proposed framework exhibited robust predictive capability, bridging in vitro dissolution data to in vivo bioequivalence outcomes, thereby offering a cost-effective and efficient strategy for formulation optimization and preclinical bioequivalence evaluation of generic drugs.